2019
DOI: 10.1177/1120700019876881
|View full text |Cite
|
Sign up to set email alerts
|

A comparative health care inventory for primary hip arthroplasty between Germany versus the Netherlands. Is there a downside effect to fast-track surgery with regard to patient satisfaction and functional outcome?

Abstract: Background: Treatment and rehabilitation protocol for hip arthroplasty differs between Germany and the Netherlands. The Dutch system promotes fast-track surgery whereas in Germany conventional care is provided with a longer hospital stay including rehabilitation. Clinical outcome, patient satisfaction and costs in both treatment protocols were compared in a prospective setup. Material and methods: This prospective cohort study included patients allocated for primary THA in 3 German and 1 Dutch hospital in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 15 publications
0
21
1
Order By: Relevance
“…Few studies have compared pain scores between outpatients and inpatients following THA and TKA during the first postoperative days, but other studies have done so with regards to the first postoperative weeks and months. These studies have found similar pain levels between inpatients and outpatients after THA and TKA (Schotanus et al 2017, Füssenich et al 2020. Schotanus et al (2017) found that 6 weeks after TKA both inpatients and outpatients had mean NRS pain scores of 2.6.…”
Section: Discussionmentioning
confidence: 79%
“…Few studies have compared pain scores between outpatients and inpatients following THA and TKA during the first postoperative days, but other studies have done so with regards to the first postoperative weeks and months. These studies have found similar pain levels between inpatients and outpatients after THA and TKA (Schotanus et al 2017, Füssenich et al 2020. Schotanus et al (2017) found that 6 weeks after TKA both inpatients and outpatients had mean NRS pain scores of 2.6.…”
Section: Discussionmentioning
confidence: 79%
“…Although the operation has a good effect on femoral neck fracture, because most of the patients are elderly, they have poor psychological endurance, slow reaction, unclear language expression, lack of understanding of diseases and operations knowledge, and worry too much that the fracture site will return to normal after the operation, which will easily lead to negative psychology such as anxiety and depression, etc. If they are not dealt with in time and effectively, it will affect the postoperative recovery of patients ( 15 , 16 ). This study showed that after treatment, the SDS and SAS scores of the patients in the observation group were significantly lower than those in the control group after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Even higher proportions are observed in Germany, where the acute care of TKA or THA patients is usually followed by 3 weeks of inpatient rehabilitation [ 45 ]. For example, Füssenich et al reported that 72% of THA patients underwent inpatient rehabilitation following surgery [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the above-mentioned rapid review showed a median of 34.1% being discharged home with supervision, but at a wide range from 0.6 to 44.2% [ 42 ]. In Germany, Füssenich et al observed that 20% of THA patients receive outpatient rehabilitation for 3 weeks, where they have 4–6 h of therapeutic interventions per day [ 46 ]. Outpatient PT can also be used alongside or after specific rehabilitation services.…”
Section: Discussionmentioning
confidence: 99%